A Study of 5‐(1, 2, 4‐Triazol‐C‐yl)tetrazol‐1‐ols: Combining the Benefits of Different Heterocycles for the Design of Energetic Materials. Issue 36 (22nd July 2013) - Dippold, Alexander A.; Izsák, Dániel; Klapötke, Thomas M.
Abstract The synthesis and full structural and spectroscopic characterization of three 5‐(1, 2, 4‐triazol‐C‐yl)tetrazol‐1‐ol compounds with selected energetic moieties including nitrimino (5), nitro (6) and azido (7) groups are reported. The influence of those energetic moieties as well as the CC connection of a tetrazol‐1‐ol and a 1, 2, 4‐triazole on structural and energetic properties has been investigated. All compounds were well characterized by various means, including IR and multinuclear NMR spectroscopy, mass spectrometry, and DSC. The molecular structures of 5–8 were determined in the solid state by single‐crystal X‐ray diffraction. The standard heats of formation were calculated on the CBS‐4M level of theory utilizing the atomization energy method, revealing highly positive values for all compounds. The detonation parameters were calculated with the EXPLO5 program and compared to the common secondary explosive RDX. Additionally, sensitivities towards impact, friction and electrostatic discharge were determined.